2008
DOI: 10.1002/jcc.21059
|View full text |Cite
|
Sign up to set email alerts
|

A combined ab initio and Franck‐Condon factor simulation study on the photodetachment spectrum of ScO2

Abstract: Restricted-spin coupled-cluster single-double plus perturbative triple excitation {RCCSD(T)} potential energy functions (PEFs) of the X(2)B2 state of ScO2 and the 1A1 state of ScO2(-) were computed, employing the augmented correlation-consistent polarized-weighted core-valence quadruple-zeta (aug-cc-pwCVQZ) basis set for Sc and augmented correlation-consistent polarized valence quadruple-zeta (aug-cc-pVQZ) basis set for O, and with the outer core Sc 3s(2)3p(6) electrons being explicitly correlated. Franck-Cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…It has been noted in ref. 18 and 19 that the computed bond angles of ScO 2 and YO 2 and their anions obtained by DFT calculations are significantly smaller than those obtained from high-level ab initio calculations. Consequently, it has been concluded that DFT methods are unreliable for the ground states of ScO 2 and YO 2 , and their anions.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…It has been noted in ref. 18 and 19 that the computed bond angles of ScO 2 and YO 2 and their anions obtained by DFT calculations are significantly smaller than those obtained from high-level ab initio calculations. Consequently, it has been concluded that DFT methods are unreliable for the ground states of ScO 2 and YO 2 , and their anions.…”
mentioning
confidence: 83%
“…20 In each case, it was found that, when correlation of the outer core (n À 1)s 2 (n À 1)p 6 electrons of the transition metal were adequately accounted for with a core-valence basis set, the RCCSD(T) method gave consistent and reliable results, and the simulated photodetachment spectrum of the transition metal dioxide anion matched very well the corresponding experimental spectrum (for details, see ref. [18][19][20]. In the present study, we have employed a similar computational strategy as used previously [18][19][20] to study low-lying electronic states of HfO 2 and the photodetachment spectrum of HfO 2 À .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Photoelectron spectra of early 3d TMO − 2 clusters have been available up to photon energies of 5 − 6.5 eV since the pioneering studies of Wang and collaborators from more than two decades ago. [46][47][48][49][50][51][52] Their structural and electronic properties have been investigated [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] in various computational studies using methods based on DFT and quantum chemistry. While these TMO − 2 molecules are isostructural with little changes in the bond angles and lengths upon changing the TM element, their frontier molecular orbitals display a wide range of spatial localization properties and have significantly varying amounts of TM 3d and O 2p contents.…”
Section: Introductionmentioning
confidence: 99%
“…This procedure has been used successfully to assign the photodetachment spectra of several triatomic negative ions. [14][15][16][17][18] However, as will be shown below, comparison between simulated and experimental spectra suggests that the experimental spectrum assigned to AlH 2 − in Ref. 1 is unlikely to be due to AlH 2…”
mentioning
confidence: 96%